Reasons for Tooth Extraction among Libyan Adults: Multi-Center Cross-Sectional Study - Elzer, Ashraf; Ensir, Hana; Elsalhi, Ali; Kablan, Rasha; Jedeh, Mohamed; Elramli, Ahmed; Eddaiki, Abdussalam (Libyan Journal of Dentistry, 2021)
Background: Tooth loss can be due to many causes, which results in many bad consequences on the dentition function and esthetics. Aims: This study was aimed to assess reasons and patterns of tooth extraction among Libyan adults. Subjects and Methods: This cross-sectional study was conducted in six Libyan cities (Benghazi, Derna, Misurata, Tripoli, Zintan, and Hoon) representing different geographical provinces of the country. Data was collected over 6-month period (from September 2016 to March 2017) using an especially designed form recruiting Libyan patients aged ≥17 years of age who visited the participating dental practices and who provided a verbal consent to take a part in the study. The reasons for tooth extraction were classified as: dental caries, severe periodontitis, trauma, impaction, orthodontics reasons, prosthodontics reasons, associated with a pathological lesions (such as cysts), failed root canal treatment, and retained primary or supernumerary teeth. Variables studied were patient’s age, gender, educational level, occupation status and type of dental clinic. SPSS software were used for data analysis and the appropriate statistical tests were applied at (p value set at 0.05). Results: The mean age of participants was 38.6 years with standard deviation (SD) of 14.83. A total of 2958 permanent teeth were extracted. The main reason for tooth extraction was dental caries 1912 (64.6%), followed by severe periodontitis 270 (9.1%), tooth impaction 231 (7.8%), prosthodontic reasons 172 (5.8%) and failed root canal treatment 157 (5.3%). The most common teeth extracted were the lower right third molar 235 (7.9%), lower left third molar 227 (7.75) and lower left first molar 187 (6.3%) respectively. The most common age group of female patients was 21-30 years as they had 779 (26.3%) teeth extracted. Low education level was the most frequent risk factor for tooth extraction 1663 (57.2%) in this group of patients. Conclusion: The result of this study indicated that dental caries and periodontal diseases still the major causes of tooth loss among Libyan adults